21 Progressive vasculo-ventricular remodelling in persistent asymptomatic left ventricular diastolic dysfunction and links with immune-inflammatory biochemical markers. (7th October 2015) - Voon, V; McDonald, K; Ledwidge, M; Watson, C; Baugh, J
Abstract : Background: The natural history of persistent asymptomatic left ventricular diastolic dysfunction (ALVDD) is not fully understood. Altered immune-inflammatory markers have been linked to extracellular matrix remodelling of myocardial interstitium and perivasculature in hypertensive animal models. We aimed to evaluate the link between immune-inflammatory markers and vasculo-ventricular remodelling in ALVDD. Methods: 91 asymptomatic hypertensive patients from the community were consecutively enrolled and subjected to guideline-based management at a dedicated Blood Pressure Unit. Demographics, Doppler-echocardiography and serum biomarkers were measured at baseline and routine 12 month follow-up. Patients with ALVDD (left atrial volume index (LAVi) > 34 ml/m 2, n = 22) and Comparators (LAVi < 34 ml/m 2, n = 44) were propensity matched to age in 1:2 ratio at baseline. From this cohort, patients with persistent ALVDD (at both timepoints, n = 10) were observed against others (n = 56). Results: ALVDD was associated with higher serum natriuretic peptide, matrix metalloproteinase (MMP)-2, LAVi and left ventricular mass index versus Comparators at baseline. All patients had mean ejection fraction (EF) 67 ± 8%. Over the follow-up duration, persistent AVLDD was associated with greater increase in monocyte chemoattractant protein-1 (924.6 ± 2420.3 vs 198.5 ± 239.4 pg/ml) and aortic root diameter (0.27 ± 0.45 vs 0.06 ± 0.27 cm) with reduction in EF (-5.4 ± 5.2 vs -0.2 ± 7.0%) versus others; all p < 0.05. Despite within-group reductions in LAVi in both groups supported by increase in anti-hypertensives with blood pressure and MMP-2 lowering, there was a significant increase in interleukin-8 and tumour necrosis factor-alpha over follow-up. Conclusion: Persistent ALVDD is associated with progressive vascular and ventricular remodelling not optimally negated by conventional anti-hypertensive therapies. These changes are linked to altered immune-inflammatory markers. The impact of inhibiting these markers requires further evaluation.